Preparation method of high-precision gel injection pressureless sintering silicon carbide ceramic water jet cutter sand pipe
Through the high-precision gel injection pressure-free sintering process, the modified silicon carbide powder and modified carbon nanotubes, combined with graphene composite silicon carbide, the problems of low yield and difficulty in mechanical processing in the preparation process of silicon carbide ceramic waterjet sand tubes in the prior art are solved, and high-precision and high-quality product production are achieved.
Patent Information
- Application Number
- CN202411852137.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the preparation of high-performance silicon carbide ceramic waterjet sand pipes, the existing technology has problems such as low yield, difficulty in machining, poor economic benefits and waste of energy, making it difficult to achieve high-precision and mass production.
High-precision gel injection pressure-free sintering process is adopted, and high-precision silicon carbide ceramic waterjet sand tube is prepared by combining modified silicon carbide powder and modified carbon nanotubes in the premix solution, combined with graphene composite silicon carbide, and casting, drying and pressure-free sintering.
It improves the toughness and mechanical strength of the silicon carbide ceramic waterjet sand pipe, enhances the bonding performance of each component, improves the stability and quality of the product, and achieves high-precision and mass production.
Smart Images

Figure BDA0005190865810000081 
Figure BDA0005190865810000082 
Figure BDA0005190865810000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic materials, and in particular to a method for preparing a high-precision gel-injected pressureless sintered silicon carbide ceramic water jet sand tube. Background Art
[0002] Sand pipe is the key to forming abrasive jet. High-pressure abrasive jet sand pipe has been troubling the water jet industry in my country for a long time. So far, the service life of cutting sand pipe and pre-mixed abrasive jet nozzle has not reached a satisfactory level.
[0003] At present, the water jet sand tubes on the market are generally made of composite tungsten carbide materials. However, compared with tungsten carbide materials, silicon carbide ceramic materials not only have excellent corrosion resistance, high wear resistance and low friction coefficient, but also have the best high-temperature mechanical properties (strength, creep resistance, etc.) among known ceramic materials, and have a lower price, so they are more suitable for the preparation of water jet sand tubes.
[0004] However, there are almost no silicon carbide ceramic water jet sand tubes in the market. The few that are available are basically first prepared by pressing to produce the external shape of the water jet sand tube, and then further processed by machining. However, this method has many defects such as low yield, difficulty in subsequent machining, low economic benefits, and energy waste. How to use a suitable molding method to prepare high-performance silicon carbide ceramic water jet sand tubes, improve their yield, ensure their accuracy, and assist in mass production is a problem that needs to be urgently solved in the market. Summary of the invention
[0005] In order to improve the product quality of the prepared silicon carbide ceramic water jet sand tube, the present application provides a method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube.
[0006] The present application provides a method for preparing a high-precision gel-injected pressureless sintered silicon carbide ceramic water jet sand tube using the following technical solution: A method for preparing a high-precision gel-injected pressureless sintered silicon carbide ceramic water jet sand tube comprises the following steps: S1, pouring the premixed liquid into a mold and solidifying it to obtain a green body; S2, taking the solidified green body out of the inner mold, and then putting the outer mold and the green body into a polyethylene glycol solution for drying, the green body shrinks when drying in the polyethylene glycol liquid, and demolding is completed; S3, drying the demoulded green body on a drying device, vacuum heating, and obtaining a dried green body; S4, performing pressureless sintering on the dried embryo body, and obtaining a silicon carbide ceramic water jet sand tube after sintering; The premixed liquid comprises monomers, a cross-linking agent, a dispersant, a defoaming agent, modified silicon carbide powder, a sintering aid and tetramethylammonium hydroxide, and the modified silicon carbide powder comprises graphene-composite silicon carbide and modified carbon nanotubes.
[0007] By adopting the above technical scheme, a silicon carbide ceramic water jet sand tube is prepared by a gel injection molding process. The modified silicon carbide powder in the premix is prepared by graphene composite silicon carbide, modified carbon nanotubes and a binder. Silicon carbide is a strong covalent bond compound. After sintering, it can strengthen the grain boundary and refine the grains, thereby improving the toughness of the prepared silicon carbide ceramic, so that the mechanical strength of the material is improved. After the silicon carbide is improved by graphene, the toughness of the silicon carbide ceramic water jet sand tube can be further improved, thereby improving the bonding ability and further improving the quality of the prepared product. At the same time, the modified carbon nanotubes are added. The carbon nanotubes have good mechanical properties and a high aspect ratio, which can significantly improve the strength and toughness of the product, and also play a role in improving the bonding performance of each component and improving the deformation caused by shrinkage, further improving the stability of the prepared product.
[0008] Preferably, the modified carbon nanotubes include carbon nanotubes, white carbon black, methacrylic acid and zinc oxide.
[0009] By adopting the above technical solution, the carbon nanotubes have a high aspect ratio and strength and good mechanical strength. However, because their aspect ratio is too large, there is a nanosize effect, and the carbon nanotubes have fewer surface active groups and poor compatibility in the system. Ordinary carbon nanotubes will agglomerate. After the carbon nanotubes are modified by acrylic acid, the number of groups on the surface of the carbon nanotubes is increased, so that the compatibility of the carbon nanotubes in the system is improved. At the same time, the dispersibility of the carbon nanotubes in the system is improved, and the stability of the prepared product is further improved.
[0010] Preferably, the modified carbon nanotubes are prepared by the following method: The carbon nanotubes are mixed with methacrylic acid, stirred after heating, and then zinc oxide and white carbon black are added, and the stirring is continued. During the stirring process, methacrylic acid is added, and after stirring, the mixture is washed and dried to obtain modified carbon nanotubes.
[0011] By adopting the above technical solution, methacrylic acid and zinc oxide react in situ to generate zinc methacrylate, and carbon nanotubes are coated at the same time to finally obtain modified carbon nanotubes. The dispersion performance of the modified carbon nanotubes is improved, thereby further improving the stability of the product.
[0012] Preferably, the mass ratio of the carbon nanotubes, white carbon black, methacrylic acid and zinc oxide is 1:0.5:(1.4-1.6):0.5.
[0013] By adopting the above technical solution, preferably the mass ratio of carbon nanotubes, white carbon black, methacrylic acid and zinc oxide is within the above range, which can further improve the stability of the prepared modified carbon nanotubes.
[0014] Preferably, the graphene-composite silicon carbide is prepared by the following method: Silicon carbide nanoparticles are mixed with anhydrous ethanol, and ultrasonically dispersed to obtain a silicon carbide dispersion. The silicon carbide dispersion is irradiated by a laser. Subsequently, the laser-irradiated silicon carbide dispersion is centrifuged and washed. The washed powder is mixed with hydrofluoric acid and hydrochloric acid, stirred until acidic, washed and centrifuged again, and dried to obtain graphene composite silicon carbide.
[0015] By adopting the above technical solution, after laser bombardment on the surface of silicon carbide nanoparticles, the chemical bonds in silicon carbide can be broken, so that Si atoms sublime, C atoms and C atoms combine with each other to form graphene, and continuously form a coating structure. The generated graphene is closely attached to the surface of the silicon carbide nanoparticles and continuously extends to form a graphene floating belt, so as to promote the tightness of the bonding between graphene and silicon carbide, thereby improving the quality of the product.
[0016] Preferably, the mass ratio between the modified carbon nanotubes and the graphene-composite silicon carbide is (0.085-0.095):1.
[0017] By adopting the above technical solution, the mass ratio between the modified carbon nanotubes and the graphene-composite silicon carbide is preferably within the above range, which can further improve the stability of the prepared modified silicon carbide powder.
[0018] Preferably, the mass ratio of the monomer to the cross-linking agent is (10-15):1, the defoaming agent accounts for 0.1-0.2% of the ceramic powder, and the sintering aid accounts for 1-2.5% of the ceramic powder.
[0019] Preferably, the mass ratio of the monomer to the cross-linking agent is (10-15):1, the defoaming agent accounts for 0.1-0.2% of the ceramic powder, and the sintering aid accounts for 1-2.5% of the ceramic powder.
[0020] Preferably, the defoaming agent includes n-octanol, the sintering aid includes carbon and silicon carbide, the catalyst includes tetramethylethylenediamine, and the initiator includes ammonium persulfate.
[0021] Preferably, the premixed slurry is prepared by the following method: The monomer and the cross-linking agent are added to water, stirred and mixed, and then a dispersant, a defoaming agent, silicon carbide powder and a sintering aid are added. Then, tetramethylammonium hydroxide is added, and the mixture is ball mixed for 2 hours. Then, vacuum degassing is performed to obtain a premixed liquid. A catalyst and an initiator are added to the premixed liquid to obtain a premixed slurry.
[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, the modified silicon carbide powder prepared by combining graphene with silicon carbide and modified carbon nanotubes has good toughness, and at the same time improves the bonding ability between the components in the system, thereby increasing the solid content of the prepared green body. The modified carbon nanotubes have a high aspect ratio, which improves the strength and toughness of the product, further improves the bonding performance between the components, and improves the shrinkage deformation phenomenon of the product, thereby improving the stability of the prepared product; 2. The surface of carbon nanotubes is modified by acrylic acid to increase the number of groups on the surface of carbon nanotubes, thereby improving the compatibility of carbon nanotubes in the system. The modified carbon nanotubes can be evenly dispersed in the system, thereby improving the stability of the prepared modified silicon carbide powder to improve product quality; 3. After laser bombardment on the surface of silicon carbide nanoparticles, the chemical bonds in silicon carbide are broken, causing Si atoms to sublime, and C atoms to combine with C atoms to form graphene, and continuously form a coating structure. The generated graphene is tightly attached to the surface of silicon carbide particles and continues to extend to form a graphene floating belt, which promotes the tightness of the bonding between graphene and silicon carbide and further improves the product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the exploded structure of the mold in the embodiment of the present application.
[0024] Figure 2 It is a partial cross-sectional schematic diagram used to illustrate the structure of the drying device in the embodiment of the present application.
[0025] Figure 3 This is a sintering tooling diagram in an embodiment of the present application.
[0026] Description of reference numerals: 1. Sand tube cover; 11. Feed inlet; 2. Sand tube outer mold; 21. First outer mold; 22. Second outer mold; 23. Casting trough; 3. Sand tube base; 4. Drying equipment; 41. Machine body; 42. First rolling shaft; 43. Second rolling shaft; 44. Protective shell. DETAILED DESCRIPTION
[0027] The following combination Figure 1 to Figure 2 This application is described in further detail.
[0028] The embodiment of the present application discloses a method for preparing a high-precision gel-injected pressureless sintered silicon carbide ceramic water jet sand tube.
[0029] Reference Figure 1The mold includes a sand tube cover 1, a sand tube outer mold 2 and a sand tube base 3. The sand tube outer mold 2 includes a first sand tube outer mold 21 and a second sand tube outer mold 22. The first sand tube outer mold 21 and the second sand tube outer mold 22 are fixed by positioning pins. The sand tube outer mold 2 and the sand tube cover 1 are fixed by positioning pins. The sand tube cover 1 is provided with a feed port 11. Five casting grooves 23 are provided in the sand tube outer mold 2. The slurry is poured into the middle casting groove 23 of the sand tube outer mold 2 through the feed port 11 for casting. Through the flow groove of the sand tube base 3, all casting grooves 23 except the middle one are cast from the bottom to the top by using the U-tube principle, and finally the casting is completed.
[0030] Reference Figure 2 The drying device 4 includes a body 41, a first rolling shaft 42, and a second rolling shaft 43. Both ends of the first rolling shaft 42 are connected to the inner wall bearing of the body 41. The first rolling shaft 42 and the second rolling shaft 43 are parallel to each other and are located at the same height. The first rolling shaft 42 and the second rolling shaft 43 have the same rotation direction. The first rolling shaft 42 and the second rolling shaft 43 are externally connected by a pulley. One end of the first rolling shaft 42 passes through the body 41 and is connected to a rotating motor to drive the first rolling shaft 42 to rotate. The demolded blank is placed on the rolling shaft and rotated to reduce the deformation of the blank during drying. The drying device 4 is also provided with a protective shell 44. In the embodiment of the present application, the protective shell 44 is a transparent glass cover. The protective shell 44 is fixedly connected to the body 41 to seal the drying device 4 as a whole. In other embodiments, the protective shell 44 can also be detachably connected to the body 41 so that the protective shell 44 can be opened by a staff member. A temperature controller with an adjustable heating rate is also installed inside the body 41 to dry the blank.
[0031] The present application is further described in detail below with reference to the embodiments: Description of raw materials: All raw materials in the embodiment can be obtained commercially; wherein, the crosslinking agent is N,N'-methylenebisacrylamide (CAS No.: 110-26-9), the monomer is acrylamide (CAS No.: 79-06-1), the dispersant is a mixture of dispersant CE64 and dispersant SOPA (model: DYSP-270) in a mass ratio of 1:1; the defoaming agent is n-octanol (CAS No.: 111-87-5); the sintering aid is a mixture of carbon and boron carbide in a mass ratio of 1:1; the catalyst is tetramethylethylenediamine (CAS No.: 110-18-9), and the initiator is 5% by mass of ammonium persulfate.
[0032] Example 1 Preparation of graphene composite silicon carbide: Silicon carbide nanoparticles were mixed with anhydrous ethanol in a mass ratio of 1:50, and ultrasonically dispersed for 0.5 h until the bottom material was precipitated to obtain a silicon carbide dispersion. The silicon carbide dispersion was irradiated by a laser for 20 min, and stirred during the irradiation process to prevent the particles from sinking to the bottom. Subsequently, the laser-irradiated silicon carbide dispersion was centrifuged and washed with deionized water. The centrifuged powder was mixed with hydrofluoric acid and hydrochloric acid, stirred until acidic, and acid-washed three times. Finally, it was washed with anhydrous ethanol, centrifuged, and dried at 60°C for 12 h to obtain graphene composite silicon carbide.
[0033] Preparation of modified carbon nanotubes 147.06 g of carbon nanotubes were mixed with 154.41 g of methacrylic acid (CAS No.: 79-41-4), heated to 60°C, stirred at 1500 r / min for 5 min, and then 73.53 g of zinc oxide and 73.53 g of white carbon were added, and stirring was continued. 51.47 g of methacrylic acid was added during the stirring process. After stirring, the mixture was washed with ethanol and dried at 80°C for 6 h to obtain modified carbon nanotubes.
[0034] Preparation of modified silicon carbide powder: 156.68 g of modified carbon nanotubes and 1843.32 g of graphene-composite silicon carbide were added to 6000 mL of N-methylpyrrolidone (CAS No.: 872-50-4), followed by ultrasonic treatment for 10 min to allow the modified carbon nanotubes and the graphene-composite silicon carbide to be fully mixed. After ultrasonic treatment, the modified carbon nanotubes and the graphene-composite silicon carbide were washed with ethanol and then dried at 70°C to obtain modified silicon carbide powder.
[0035] Preparation of master mix: Add 65g of monomer and 6.5g of cross-linking agent to 300g of deionized water, stir and mix, then add 13g of dispersant, 1.3g of defoaming agent, 1300g of silicon carbide powder and 13g of sintering aid, then add 0.085g of tetramethylammonium hydroxide, mix for 2h, then vacuum degas, add 0.1g of catalyst and 0.1g of initiator to obtain a premixed solution.
[0036] Preparation of high-precision pressureless sintered silicon carbide ceramic water jet sand tube: S1, pouring the premixed liquid into a mold and curing at 16°C to obtain a green body; S2, taking the solidified green body out of the inner mold, and then putting the outer mold and the green body into a polyethylene glycol solution for drying for 2 hours. The green body shrinks when drying in the polyethylene glycol liquid, and demolding is completed; S3, drying the demoulded green body on a drying device, and vacuum heating to 100° C. to obtain a dried green body; S4, placing the dried green body on a sintering tool for pressureless sintering, and after sintering, a silicon carbide ceramic water jet sand tube is obtained.
[0037] The temperature rise curve in step S4 is shown in Table 1.
[0038] Example 2 Preparation of graphene composite silicon carbide: Silicon carbide nanoparticles were mixed with anhydrous ethanol in a mass ratio of 1:50, and ultrasonically dispersed for 0.5 h until the bottom material was precipitated to obtain a silicon carbide dispersion. The silicon carbide dispersion was irradiated by a laser for 20 min, and stirred during the irradiation process to prevent the particles from sinking to the bottom. Subsequently, the laser-irradiated silicon carbide dispersion was centrifuged and washed with deionized water. The centrifuged powder was mixed with hydrofluoric acid and hydrochloric acid, stirred until acidic, and acid-washed three times. Finally, it was washed with anhydrous ethanol, centrifuged, and dried at 60°C for 12 h to obtain graphene composite silicon carbide.
[0039] Preparation of modified carbon nanotubes 138.89 g of carbon nanotubes were mixed with 166.68 g of methacrylic acid, heated to 60°C, stirred at 1500 r / min for 5 min, and then 69.44 g of zinc oxide and 69.44 g of white carbon were added, and stirring was continued. During the stirring process, 55.56 g of methacrylic acid was added. After stirring, the mixture was washed with ethanol and dried at 80°C for 6 h to obtain modified carbon nanotubes.
[0040] Preparation of modified silicon carbide powder: 173.52 g of modified carbon nanotubes and 1826.48 g of graphene-composite silicon carbide were added to 6000 mL of N-methylpyrrolidone, followed by ultrasonic treatment for 10 min to allow the modified carbon nanotubes and the graphene-composite silicon carbide to be fully mixed. After ultrasonic treatment, the modified carbon nanotubes and the graphene-composite silicon carbide were washed with ethanol and then dried at 70°C to obtain modified silicon carbide powder.
[0041] Preparation of master mix: Add 75g of monomer and 7.5g of cross-linking agent to 350g of deionized water, stir and mix, then add 30g of dispersant, 3g of defoaming agent, 1500g of silicon carbide powder and 37.5g of sintering aid, then add 0.2g of tetramethylammonium hydroxide, mix for 2h, then vacuum degas, add 0.2g of catalyst and 0.2g of initiator to obtain a premixed solution.
[0042] Preparation of high-precision pressureless sintered silicon carbide ceramic water jet sand tube: S1, pouring the premixed liquid into a mold and curing at 16°C to obtain a green body; S2, taking the solidified green body out of the inner mold, and then putting the outer mold and the green body into a polyethylene glycol solution for drying for 3 hours. The green body shrinks when drying in the polyethylene glycol liquid, and demolding is completed; S3, drying the demoulded green body on a drying device, and vacuum heating to 100° C. to obtain a dried green body; S4, placing the dried green body on a sintering tool for pressureless sintering, and after sintering, a silicon carbide ceramic water jet sand tube is obtained.
[0043] The temperature rise curve in step S3 is shown in Table 1.
[0044] Example 3 Preparation of graphene composite silicon carbide: Silicon carbide nanoparticles were mixed with anhydrous ethanol in a mass ratio of 1:50, and ultrasonically dispersed for 0.5 h until the bottom material was precipitated to obtain a silicon carbide dispersion. The silicon carbide dispersion was irradiated by a laser for 20 min, and stirred during the irradiation process to prevent the particles from sinking to the bottom. Subsequently, the laser-irradiated silicon carbide dispersion was centrifuged and washed with deionized water. The centrifuged powder was mixed with hydrofluoric acid and hydrochloric acid, stirred until acidic, and acid-washed three times. Finally, it was washed with anhydrous ethanol, centrifuged, and dried at 60°C for 12 h to obtain graphene composite silicon carbide.
[0045] Preparation of modified carbon nanotubes 142.86 g of carbon nanotubes were mixed with 214.28 g of methacrylic acid, heated to 60°C, stirred at 1500 r / min for 5 min, and then 71.43 g of zinc oxide and 71.43 g of white carbon were added, and stirring was continued. During the stirring process, 53.57 g of methacrylic acid was added. After stirring, the mixture was washed with ethanol and dried at 80°C for 6 h to obtain modified carbon nanotubes.
[0046] Preparation of modified silicon carbide powder: 148.15 g of modified carbon nanotubes and 1851.85 g of graphene-composite silicon carbide were added to 6000 mL of N-methylpyrrolidone, followed by ultrasonic treatment for 10 min to allow the modified carbon nanotubes and the graphene-composite silicon carbide to be fully mixed. After ultrasonic treatment, the mixture was washed with ethanol and then dried at 70° C. to obtain modified silicon carbide powder.
[0047] Preparation of master mix: Add 70g of monomer and 7g of cross-linking agent to 320g of deionized water, stir and mix, then add 21g of dispersant, 2.1g of defoaming agent, 1400g of silicon carbide powder and 25.3g of sintering aid, then add 0.143g of tetramethylammonium hydroxide, mix for 2h, then vacuum degas, add 0.15g of catalyst and 0.15g of initiator to obtain a premixed solution.
[0048] Preparation of high-precision pressureless sintered silicon carbide ceramic water jet sand tube: S1, pouring the premixed liquid into a mold and curing at 16°C to obtain a green body; S2, taking the solidified green body out of the inner mold, and then putting the outer mold and the green body into a polyethylene glycol solution for drying for 2.5 hours, the green body shrinks when drying in the polyethylene glycol liquid, and demolding is completed; S3, drying the demoulded green body on a drying device, and vacuum heating to 100° C. to obtain a dried green body; S4, placing the dried green body on a sintering tool for pressureless sintering, and after sintering, a silicon carbide ceramic water jet sand tube is obtained.
[0049] The temperature rise curve in step S3 is shown in Table 1.
[0050] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing modified carbon nanotubes, 156.25 g of carbon nanotubes, 78.125 g of white carbon black, 187.5 g of methacrylic acid, and 78.125 g of zinc oxide are used.
[0051] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing modified carbon nanotubes, 131.58 g of carbon nanotubes, 65.79 g of white carbon black, 236.84 g of methacrylic acid, and 65.79 g of zinc oxide are used.
[0052] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the modified silicon carbide powder, 113.21 g of modified carbon nanotubes and 1886.79 g of graphene composite silicon carbide are used.
[0053] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the modified silicon carbide powder, 214.29 g of modified carbon nanotubes and 1785.71 g of graphene composite silicon carbide are used.
[0054] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing the modified silicon carbide powder, only silicon carbide and graphene are mixed in a mass ratio of 1:0.1.
[0055] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the modified silicon carbide composite powder, the modified carbon nanotubes are replaced with ordinary carbon nanotubes.
[0056] Comparative Example 1 Comparative Example 1 is based on Example 3. The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the modified silicon carbide powder is replaced by ordinary silicon carbide powder.
[0057] Table 1 Vacuum drying temperature rise curve in step (3) Performance testing The samples of Examples 1-9 and Comparative Example 1 were sampled and the following performance tests were performed: (1) Surface condition after drying The wet blank was dried, and the condition of the dry blank after drying was observed and recorded. The results are recorded in Table 2.
[0058] (2) Flexural strength The bending strength of the samples was tested according to GB / T 6569-2006 Test method for bending strength of fine ceramics. Each sample was tested three times at room temperature, and the average value was taken. The test results were filled in Table 2.
[0059] (3) Hardness According to GB 16534-2009 Test Method for Hardness of Fine Ceramics at Room Temperature, a Vickers hardness tester was used to test and calculate the Vickers hardness of the sample. Each sample was tested three times and the average value was taken after measurement. The results are recorded in Table 2.
[0060] Table 2 Test results of samples of Examples 1-9 and Comparative Example 1 From Table 1, it can be seen that there is no cracking on the surface of the samples of Examples 1-3, the bending strength is 360 MPa or above, and the hardness is 25 or above, which shows that the silicon carbide ceramic water jet sand tube prepared in this application has good stability and strength.
[0061] In Example 4 and Example 5, when preparing modified carbon nanotubes, carbon nanotubes, white carbon black, methacrylic acid and zinc oxide are not within the scope defined in the present application. When the content of methacrylic acid is too little, the content of active groups connected to the surface of the carbon nanotubes is small, making it difficult to further improve the dispersion performance of the carbon nanotubes. At the same time, it is difficult to further improve the etching effect on the surface of the carbon nanotubes, making it difficult to further improve the roughness of the carbon nanotubes, and the binding ability in the system is reduced, affecting the product quality; when the content of methacrylic acid is too much, the etching of the carbon nanotubes is too large, affecting the stability of the carbon nanotubes, so that the overall stability of the system is reduced. Therefore, the performance of Example 4 and Example 5 is reduced.
[0062] In Example 6 and Example 7, when preparing modified silicon carbide powder, the mass ratio between the modified carbon nanotubes and the graphene composite silicon carbide is not within the range specified in the present application. When the content of the modified carbon nanotubes is too much or too little, it will affect the stability of the prepared premix, thereby reducing the quality of the prepared product. Therefore, the performance of Example 6 and Example 7 is reduced.
[0063] The modified silicon carbide powder in Example 8 is obtained by mixing silicon carbide and graphite. The bonding performance between ordinary mixed silicon carbide and graphene is poor, and graphene agglomerates in the system, resulting in reduced stability. Therefore, the product quality of the prepared water jet sand pipe is also reduced. Therefore, the performance of Example 8 is reduced.
[0064] In Example 9, when preparing the modified silicon carbide composite powder, the modified carbon nanotubes are replaced with ordinary carbon nanotubes. The surface of the unmodified carbon nanotubes does not have more active groups, and the compatibility in the system is difficult to improve. At the same time, the surface has not been etched, and the roughness is difficult to improve. The binding performance in the system is reduced, which affects the quality of the product. Therefore, the performance of Example 9 is reduced.
[0065] In Comparative Example 1, the modified silicon carbide powder is replaced with ordinary silicon carbide powder. The compatibility and connection strength of ordinary silicon carbide powder are difficult to improve, so the quality of the prepared product is difficult to improve. Therefore, the various performances of Comparative Example 1 are reduced.
[0066] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube, characterized in that: The steps include: S1, pouring the premixed liquid into a mold and solidifying it to obtain a green body; S2, taking the solidified green body out of the inner mold, and then putting the outer mold and the green body into a polyethylene glycol solution for drying, the green body shrinks when drying in the polyethylene glycol liquid, and demolding is completed; S3, drying the demoulded green body on a drying device, vacuum heating, and obtaining a dried green body; S4, performing pressureless sintering on the dried embryo body, and obtaining a silicon carbide ceramic water jet sand tube after sintering; The premixed liquid comprises monomers, a cross-linking agent, a dispersant, a defoaming agent, modified silicon carbide powder, a sintering aid and tetramethylammonium hydroxide, and the modified silicon carbide powder comprises graphene-composite silicon carbide and modified carbon nanotubes.
2. The method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube according to claim 1, characterized in that: The modified carbon nanotubes include carbon nanotubes, white carbon black, methacrylic acid and zinc oxide.
3. The method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube according to claim 2, characterized in that: The modified carbon nanotubes are prepared by the following method: The carbon nanotubes are mixed with methacrylic acid, stirred after heating, and then zinc oxide and white carbon black are added, and the stirring is continued. During the stirring process, methacrylic acid is added, and after stirring, the mixture is washed and dried to obtain modified carbon nanotubes.
4. The method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube according to claim 3, characterized in that: The mass ratio of the carbon nanotubes, white carbon black, methacrylic acid and zinc oxide is 1:0.5:(1.4-1.6):0.
5.
5. The method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube according to claim 1, characterized in that: The graphene composite silicon carbide is prepared by the following method: Silicon carbide nanoparticles are mixed with anhydrous ethanol, and ultrasonically dispersed to obtain a silicon carbide dispersion. The silicon carbide dispersion is irradiated by a laser. Subsequently, the laser-irradiated silicon carbide dispersion is centrifuged and washed. The washed powder is mixed with hydrofluoric acid and hydrochloric acid, stirred until acidic, washed and centrifuged again, and dried to obtain graphene composite silicon carbide.
6. The method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube according to claim 5, characterized in that: The mass ratio between the modified carbon nanotubes and the graphene-composite silicon carbide is (0.085-0.095):
1.
7. The method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube according to claim 1, characterized in that: The mass ratio of the monomer to the cross-linking agent is (10-15):1, the defoaming agent accounts for 0.1-0.2% of the ceramic powder, and the sintering aid accounts for 1-2.5% of the ceramic powder.
8. The method for preparing a high-precision gel-injection pressureless sintered silicon carbide ceramic water jet sand tube according to claim 1, characterized in that: The defoaming agent includes n-octanol, the sintering aid includes carbon and silicon carbide, the catalyst includes tetramethylethylenediamine, and the initiator includes ammonium persulfate.
9. The method for preparing a high-precision gel-cast pressureless sintered silicon carbide ceramic water jet sand tube according to claim 1, characterized in that: The premixed slurry is prepared by the following method: The monomer and the cross-linking agent are added to water, stirred and mixed, and then a dispersant, a defoaming agent, silicon carbide powder and a sintering aid are added. Then, tetramethylammonium hydroxide is added, and the mixture is ball mixed for 2 hours. Then, vacuum degassing is performed to obtain a premixed liquid. A catalyst and an initiator are added to the premixed liquid to obtain a premixed slurry.
Citation Information
Patent Citations
Cyclopentadiene-modified carbon nanotube / rubber composite material and preparation method thereof
CN104650400A
Quick in-situ preparation method of noctiluca-shaped graphene wrapped silicon carbide microsphere
CN107686761A
Modified composite material using carbon nanotubes and graphene and preparation method thereof
CN108517123A
Preparation method of silicon carbide ceramic
CN117923907A
Preparation method of gel injection pressureless sintering silicon carbide ceramic water jet cutter sand pipe
CN118324535A
Cited By
Wear-resistant rubber-plastic composite material for high-pressure air pipe and production method thereof
CN120098387A
A wear-resistant rubber-plastic composite material for high-pressure air pipes and its production method
CN120098387B
Acidic dry material for intermediate frequency furnace based on micronized raw materials and preparation method of acidic dry material
CN120398526A